Post-Basic Nursing: Specialisation or Specialty? A Concept Analysis - Mohd Said Nurumal; Muhammad Kamil Che Hasan; Thandar Soe @ Sumaiyah Jamaludin (INTERNATIONAL JOURNAL OF CARE SCHOLARS, 2026)
Background: Post-basic nursing education is crucial for enhancing clinical competencies. Despite its longstanding implementation in Malaysia and globally, uncertainty remains whether post-basic nursing should be conceptualized as specialisation (pengkhususan) or specialty (kepakaran). This conceptual ambiguity contributes to inconsistencies in nursing education, professional credentialing, career progression, and policy development. This conceptual ambiguity creates inconsistencies in education, credentialing, and policy. Methods: Using Walker and Avant’s framework, this concept analysis examined post-basic nursing through a narrative literature review of 21 sources. Results: The analysis demonstrated that post-basic nursing is characterized primarily by focused clinical competency development, practice-oriented education, and service-driven training, aligning it closely with specialisation. In contrast, specialty encompasses broader professional attributes, including advanced theoretical knowledge, research capability, evidence-based practice, leadership, autonomous clinical decision-making, and scholarly contribution. Although many international frameworks increasingly link specialty practice with postgraduate education, regulatory requirements differ across nations; some healthcare systems continue to recognize specialty through structured post-registration certification and extensive clinical experience rather than graduate degrees alone. Within the Malaysian context, findings indicate that post-basic nursing aligns with clinical specialisation, whereas postgraduate education provides the primary pathway for acquiring advanced disciplinary knowledge and scholarly expertise in accordance with the Malaysian Qualifications Framework. Conclusion: Clarifying these concepts supports more cohesive educational pathways, professional credentialing, workforce planning, and career advancement, ultimately strengthening nursing as both a clinical profession and a scholarly discipline.